2021
DOI: 10.1111/1346-8138.15941
|View full text |Cite
|
Sign up to set email alerts
|

Case of pemphigoid vegetans with autoantibodies against the BP180 C‐terminal domain and BP230 antigen

Abstract: Pemphigoid vegetans is a rare variant of bullous pemphigoid characterized by vegetative and purulent lesions of the groin, axillae, thighs, hands, eyelids, and perioral regions. 1 The clinical features and histological findings of pemphigus vegetans and immunohistochemical characteristics of bullous pemphigoid are shown. Only 11 cases have been reported in the English-language literature to date. [1][2][3][4][5][6][7][8][9][10][11] Here, we describe a case of pemphigoid vegetans in which autoantibodies against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…In our case, a linear IgA deposit at the dermo-epidermal junction was found by direct immunofluorescence, as reported by Ogasawara et al 11 Indirect immunofluorescence was positive in nine cases. 1 3 , 5 , 6 , 8 , 10 , 12 , 13 Immunoblotting analysis has been reported in five cases. 3 , 5 , 6 , 10 , 12 BP230 autoantibodies were positive in every case, and three cases had BP180 autoantibodies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our case, a linear IgA deposit at the dermo-epidermal junction was found by direct immunofluorescence, as reported by Ogasawara et al 11 Indirect immunofluorescence was positive in nine cases. 1 3 , 5 , 6 , 8 , 10 , 12 , 13 Immunoblotting analysis has been reported in five cases. 3 , 5 , 6 , 10 , 12 BP230 autoantibodies were positive in every case, and three cases had BP180 autoantibodies.…”
Section: Discussionmentioning
confidence: 99%
“… 1 3 , 5 , 6 , 8 , 10 , 12 , 13 Immunoblotting analysis has been reported in five cases. 3 , 5 , 6 , 10 , 12 BP230 autoantibodies were positive in every case, and three cases had BP180 autoantibodies. 5 , 8 , 12 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…may contribute to the development of vegetating lesions because Staphylococcus spp. has been detected in the vegetative lesions of pemphigus vegetans and pemphigoid vegetans patients (7)(8)(9). Several studies revealed that S. aureus can modify the immunological milieu in the colonization region (10,11).…”
Section: Discussionmentioning
confidence: 99%